Good business : exercising effective and ethical leadership - Mayer, Don; O'Toole, James (Routledge, 2010)
A collection of essays that addresses the increasingly important topics of corporate ethics, social responsibility, and sustainability in the context of effective global business strategies. It demonstrates that ethics is not peripheral, or in addition to, the central concerns of business